Reasons for declining participation in inpatient research among historically minoritized racial and ethnic communities: A scoping review - Poyani Bavishi; Alyssa A. Grimshaw; Oscar F. Rojas Perez; Brian D. Kiluk; E. Jennifer Edelman (Contemporary Clinical Trials Communications)
Background: To promote equitable recruitment for studies conducted in the inpatient hospital setting, we sought to characterize reasons why individuals, both from historically minoritized racial and ethnic groups and the broader patient population, refuse participation in clinical trials within inpatient settings. Methods: An exhaustive search of the literature was conducted in Cochrane Library, Google Scholar, Embase, MEDLINE, PubMed, Scopus, and Web of Science databases to find relevant articles published from the inception of each database to April 30, 2023. Studies recruiting patients during their inpatient stay and reporting reasons for refusing participation in clinical trials met the inclusion criteria. Results: The search resulted in 2264 citations, of which 22 were included. Fourteen did not report data related to race, while 19 reported no ethnicity data. Reasons for refusal across trials included study burden and inconvenience (n = 16), transportation and logistical issues (n = 13), lack of interest in research (n = 12), and refusal to be randomized (n = 10). Prominent concepts included the importance of incorporating social support systems in consenting processes, lack of efforts to include data or recruitment efforts for individuals from minoritized groups, and physician involvement in recruitment. Discussion: To enhance participation among historically minoritized communities in clinical trials, greater efforts must be made to collect demographic information and document refusal reasons to inform future recruitment methods. Strategies include proactively accounting for culture and language differences in study design and recruitment and intentionally engaging social support networks. Limiting study burden and logistics and optimizing collaborations between clinical and research teams would promote accessibility and foster patient trust.